Family context and its relationship with parental involvement in the education of secondary school children - Zakaria, Abd Razak; Hasim, Zuwati; Mohd Salleh, Umi Kalsum; Yusoff, Jal Zabdi Mohd (2013)
This study aimed at investigating the extent parents involvement in educating their secondary school children. The participants consisted of 950 Form Four students from government assisted secondary schools in Malaysia. The questionnaires were administered to the sample in the state of Selangor. The findings of the study revealed that interaction and communication, parenting practices, leisure, openness and acceptance were the predictive factors and had a positive relationship with parental involvement in education of secondary school children. Multiple regression analysis showed that the component of family context contributed 44.5 percent to the involvement of parents at home as compared to only 16.0 percent for involvement of parents in school. Overall, it was found that family context contributed 41.1 percent to the involvement (home and school). Of greater interest is that this study found that involvement of parents in education of their secondary school children was not the main factor for their children’s achievement in learning. The children obtained high academic achievement even without the parents involvement. A conducive and harmonious family context was able to motivate the children to succeed in their studies. Hence it can be concluded that although family involvement is important in raising the academic achievement of children, the family context is the main factor in influencing the children’s academic achievement. To conclude, it would be more meaningful if efforts aimed at children’s academic success in school utilize a more holistic strategy by strengthening the family institution and creating healthy family relationships.